A bibliometric study of financial innovation development trends - Abdinova, M.Kh.; Kazykeshova, A.T.; Parmanova, R.S.; Arystanbayeva, S.S. (Karagandy University of the name of acad. E.A. Buketov, 2024)
Object: The purpose of this article is to identify and analyse the most influential authors, publications, countries, journals on financial innovation and the key trends in their development of financial innovations using bibliometric method based on Web of Science Core Collection data using VOSviewer. Methods: This study used the quantitative and qualitative method. The PRISMA approach helped to sort out 942 articles on the financial innovation topic. The science mapping analysis as the citation analysis of documents, authors and countries, and co-occurrence analysis of all keywords was applied to show the main research trends in financial innovation field. Findings: The most productive country is the USA. The most productive author is Oskooee, Mehdi Bahmani. The Journal of Banking Finance published the greater number of papers which is 29. The trends were specified using the clusters. So, business innovation, economic growth, fintech, corporate innovation and financial inclusion are popular trends in financial innovation development. Conclusions: Financial innovation influence our daily life through financial sector, specifically banking sector and fintech products and services. Popularity increases in the fintech products and services, eco and green innovation that affect the company’s performance and image. Developed countries have greater impact to promote this topic.
Object: The purpose of this article is to identify and analyse the most influential authors, publications, countries, journals on financial innovation and the key trends in their development of financial innovations using bibliometric method based on Web of Science Core Collection data using VOSviewer. Methods: This study used the quantitative and qualitative method. The PRISMA approach helped to sort out 942 articles on the financial innovation topic. The science mapping analysis as the citation analysis of documents, authors and countries, and co-occurrence analysis of all keywords was applied to show the main research trends in financial innovation field. Findings: The most productive country is the USA. The most productive author is Oskooee, Mehdi Bahmani. The Journal of Banking Finance published the greater number of papers which is 29. The trends were specified using the clusters. So, business innovation, economic growth, fintech, corporate innovation and financial inclusion are popular trends in financial innovation development. Conclusions: Financial innovation influence our daily life through financial sector, specifically banking sector and fintech products and services. Popularity increases in the fintech products and services, eco and green innovation that affect the company’s performance and image. Developed countries have greater impact to promote this topic.
Keywords: financial innovation; VOSviewer. PRISMA; PRISMA; VOSviewer.; Web of Science; bibliometric study; financial technology; fintech; библиометриялық зерттеу; қаржылық технология; финтех; қаржылық инновация; финансовые инновации; финансовые технологии; библиометрическое исследование6